2017
DOI: 10.1021/acs.biomac.7b00162
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Copolymers Inhibit Digestive Enzymes by Surface Recognition

Abstract: This account presents a general method for the construction of polymeric surface binders for digestion enzymes. Two prominent parts, namely, the modification of the copolymer composition and the screening assay for the most powerful inhibitors are both amenable to parallelization. The concept hinges on the appropriate selection of amino-acid-selective comonomers, their free radical copolymerization, and subsequent screening of the resulting copolymer library for efficient enzyme inhibition. A microscale synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…In these works, the authors demonstrated that screening large numbers of copolymers synthesized by free‐radical polymerization was a viable strategy for identifying strong binding interactions between synthetic polymers and immunoglobulins, [ 40 ] or digestive enzymes. [ 41 ]…”
Section: Fundamental Association Mechanisms Between Synthetic Polymer...mentioning
confidence: 99%
See 1 more Smart Citation
“…In these works, the authors demonstrated that screening large numbers of copolymers synthesized by free‐radical polymerization was a viable strategy for identifying strong binding interactions between synthetic polymers and immunoglobulins, [ 40 ] or digestive enzymes. [ 41 ]…”
Section: Fundamental Association Mechanisms Between Synthetic Polymer...mentioning
confidence: 99%
“…In these works, the authors demonstrated that screening large numbers of copolymers synthesized by free-radical polymerization was a viable strategy for identifying strong binding interactions between synthetic polymers and immunoglobulins, [40] or digestive enzymes. [41] In another complementary strategy for synthetic polymerprotein binding, Xu and co-workers analyzed the dispersity of amino acid residues on the surfaces of folded proteins to provide design criteria for synthetic heteropolymers. [42] Interestingly, computational analysis of model proteins such as horseradish peroxidase suggested many small patches (1-2 nm) of neutral hydrophilic, hydrophobic, positively, or negatively charged groups on the folded protein surfaces, with interpatch distances of 1-2 nm.…”
Section: Targeted Recognition Based On Specific Biomolecular Motifsmentioning
confidence: 99%
“…Additionally, typically, PPIs are larger than 1000 Å 2 and involve more than 20 amino acid contacts. 3,4) Synthetic polymers, such as dendrimers, 5) linear polymers, [6][7][8] and polymer nanoparticles (NPs), 9,10) have the potential to work as protein affinity reagents by mimicking protein-protein interactions 11) (Fig. 1b).…”
Section: Protein Affinity Reagentsmentioning
confidence: 99%
“…Non-covalent polymer-protein binding studies, sometimes involvingd elivery experiments, is ab road field, and additional reports relatedt ot his topic that highlight various binding interactions and characterization methods can be found in Refs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71].B inding studies showcasing availablet echniques could potentially contain criticali nformation necessary for future protein-delivery optimization studies and should not be overlooked.…”
Section: Other Non-covalent Protein-basedcomplexes For Deliverymentioning
confidence: 99%